The neuroprotective effect of memantine on serum S100-B levels after on-pump coronary artery bypass graft surgery: A randomized clinical trial - Shervin Ziabakhsh Tabary; Parham Ziabakhsh Tabary; Alireza Sanei Motlagh (Babol University of Medical Sciences, 2022)
Background: Brain injury is one of the complications of open heart surgery. Glutamate plays a key role in this process. In this study, we evaluated the neuroprotective effect of memantine as NMDAR inhibitor in patients undergoing on-pump coronary artery bypass graft surgery (CABG). Methods: From July 2019 to May 2020, thirty-four consecutive patients selected for elective isolated on-pump coronary artery bypass graft surgery (CABG) enrolled in the trial. Patients were randomly assigned into two groups; memantine and the control group. For the memantine group, 10 mg of memantine twice daily was administered at least 72 h before surgery. Venous blood samples were collected before surgery (T1), at the end of cardiopulmonary bypass (CPB) (T2), 6h and 24h after CPB (T3 and T4). Serum concentration of S100-B was measured by enzyme-linked immunosorbent assay (ELISA) technique. Results: Serum S100-B increased during CPB with a peak plasma concentration at the termination of CPB. Then it gradually decreased during the first 24 hours in both groups (P=0.001). The mean S100-B levels were significantly lower in the memantine group compared to the control group at the termination of CPB (0.863±0.203 μg/l vs 1.117±0.304 μg/l), at 6 hours post-CPB (0.731±0.168 μg/l vs 0.938±0.206 μg/l), and 24 hours post-CPB (0.595±0.189 μg/l vs 0.852±0.227 μg/l), respectively (P=0.023). The mean level of serum S100-B in memantine group was about 0.19 μg/l less than the control group during the study (CI, 0.07 to 0.30; P=0.001). One (6.2%) patient in the control group had post-operative left arm paresthesia Conclusion: Administration of memantine before on-pump CABG can attenuate the post-operative concentrations of serum S100-B, which may reduce cerebral damage during surgery.